Reliability of Language Skills Assessment Results - Mohammad Adnan Latief (Universitas Negeri Malang, 2016)
The meaning of reliability is discussed in contrast to the meaning of validity. While validity of language assessment results refers to the degree of correctness of representation of the language skill being assessed, reliability of language skill assessment results refers to the degree of preciseness of the representation of the language skill being assessed. The farther the language skills assessment result deviates from the actual level of the skill being assessed, the bigger the error is, and the lower the reliability of the language skills assessment is. Estimating reliability means collecting evidence of consistency